Reducing Lead time in High-Mix Low-Volume Conformal Coating : A Study at PBA Production, SAAB Järfälla - Livingstone, Agnes (2016)
This report is the final thesis project for a Master of Science in Industrial Design Engineering at Luleå University of Technology, conducted during a 20 week period between September 2015 and January 2016. The purpose of this master thesis was to evaluate and analyse a PCB conformal coating process at Saab EDS in Järfälla, Sweden. The analysis was done with the in order to find ways to reduce lead time and increase efficiency in a sustainable manner within this process.At Saab EDS in Järfälla electronic circuit boards are assembled for use in electronic warfare - and counter measure systems. Since these PCB assemblies are used in very demanding and harsh environments (i.e. on military airplanes) they must be conformal coated. Conformal coating is a process whereby a protective film is applied to the PCB assembly. This process is tedious with a lot of manual application and correction, despite the fully automated coating equipment. There is also a predicted increase in both volume and product complexity making the current process insufficient to meet those demands. Reducing lead time in the process is however not straight forward since the production displays characteristics of high-mix/low-volume production.The project was conducted using a traditional development process where there was first a thorough review of available literature on the subject of lead time reduction in high-mic/low-volume environments and on the subject of efficiency in conformal coating. The current state was then mapped and analysed using a mix of different well-known methods such as value stream mapping and hierarchical task analysis. The current state analysis resulted in a number of process requirements meant to alleviate the most critical issues. Solutions to these issues where developed using a high level of participation from the operators and company stakeholders to identify viable and reliable solutions.The final results pointed to three different areas as having the largest potential to reduce lead time and increase efficiency ...